Avaliação do uso de barreira acústica para escolas municipais em Porto Alegre - Soares, Fabiano Silva (Universidade do Vale do Rio dos Sinos, 2018)
The disorderly growth of cities has contributed to a significant increase of noise pollution, at the same time as it causes frictions between neighbors, jeopardizing the well-being of communities. One of the alternatives used to reduce these effects is the adoption of acoustic barriers, since it is one of the most effective solutions to reduce the propagation of sound in open space. In the scenario, the school has always been seen as a sensitive receptor, and hardly ever considered a sound emitter, and this is the research subject of the present dissertation. Therefore, this work proposes to discuss the use of acoustic barriers as a way to solve the free propagation of emitted sound during recreation activities in two educational facilities in the city of Porto Alegre. The main problem consists in reducing the levels of sound pressure that reach neighboring buildings, as a way to guarantee the observance of levels established by the Associação Brasileira de Normas Técnicas (ABNT – Brazilian Association of Technical Norms) in the norms NBR 10151 and 10152. As it was grounded in real situations, the case study involved field surveys to assess school and neighboring building physical spaces, laboratory tests to determine the sound absorption coefficient, and field tests to determine the levels of sound pressure emitted by children at the schools. The field tests showed that noise levels inside the neighboring buildings and outside on the playgrounds were above the ones established in the norms. For the continuity of the study, a sound barrier prototype was built, using concepts of noise reflection and absorption, as the Helmholtz resonator, and then tested in laboratory. According to the results obtained with the sample, a weighted sound absorption coefficient (αw) of 0.7 was obtained. The CadnaA® software was the tool used to conduct simulations of sound barrier projects in both schools. A reduction of 15 dB was demonstrated at Jardim Camaquã School, whilst a 5 dB reduction was demonstrated at Unidos da Paineira School, being that the use of inclined top finish only represented significant reduction at Jardim Camaquã School. The use of sound barriers was proved relevant, but even so the levels established by norm were not reached.
Keywords: Barreira acústica; Ruído ambiental; Conforto acústico; Acoustic barriers; Environmental noise; Acoustic comfort; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo